2018
DOI: 10.1111/1744-9987.12764
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Plasma Ghrelin Levels in Hemodialysis Patients

Abstract: The beta value means the standardized regression coefficient. R 2 value is coefficient of determination. BMD, bone mineral density; CRP, C-reactive protein; Kt/V urea , dialysis dose; PG, pepsinogen. The beta value means the standardized regression coefficient. R 2 value is coefficient of determination. BMD, bone mineral density;CRP, C-reactive protein; Kt/V urea , dialysis dose; PG, pepsinogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We cannot rule out the possibility that some of the variability in levels was due to the assay used which measures both acyl-ghrelin, considered the active form of ghrelin, plus des-acyl ghrelin. Other characteristics associated with differences in ghrelin levels, such as BMI, insulin resistance, and sex [ 48 , 49 ] were similar between groups. Racial differences in ghrelin have been observed: African Americans had higher fasting levels and impaired postprandial suppression[ 50 – 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot rule out the possibility that some of the variability in levels was due to the assay used which measures both acyl-ghrelin, considered the active form of ghrelin, plus des-acyl ghrelin. Other characteristics associated with differences in ghrelin levels, such as BMI, insulin resistance, and sex [ 48 , 49 ] were similar between groups. Racial differences in ghrelin have been observed: African Americans had higher fasting levels and impaired postprandial suppression[ 50 – 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to arrive fasted and rested at 08:00 a.m. and to consume their last meal on the previous day before 10:00 p.m. Previous studies have reported gender differences and influence of the menstrual circle on acylated ghrelin levels [47][48][49]. Therefore, we chose to conduct our study on male subjects only.…”
Section: Subjectsmentioning
confidence: 99%
“…The release of inflammatory cytokines is inhibited by ghrelin [17]. Additionally, it was demonstrated that the level of the hormone Ghrelin was significantly lower in females than in males (p≤0.05).These findings deviate from earlier research [18]. To elucidate gender disparities in ghrelin levels in hemodialysis (HD) patients, ghrelin levels were evaluated, and the link between ghrelin and pertinent clinical indicators was studied by gender.…”
Section: Resultsmentioning
confidence: 77%